Impact of social media on triggering nonsuicidal self-injury in adolescents: a comparative ambulatory assessment study - Andreas Goreis; Dorothy Chang; Diana Klinger; Heidi-Elisabeth Zesch; Bettina Pfeffer; Sofia-Marie Oehlke; Ulrich W. Ebner-Priemer; Laurence Claes; Paul L. Plener; Oswald D. Kothgassner (Borderline Personality Disorder and Emotion Dysregulation)
Abstract Background Nonsuicidal self-injury (NSSI) is a prevalent and concerning behavior among adolescents, often triggered by negative interpersonal events. As social media is essential in the daily life of adolescents, gaining a better understanding of the impact of negative online events on NSSI urges and behaviors, distinct from that of real-life events, is warranted. Methods We recruited 25 adolescents with a history of NSSI and 25 healthy controls. Participants reported on their stress, affect, and NSSI urges four times daily over seven days using ambulatory assessment. We examined the immediate effects of negative events in real-life and on social media on these psychological outcomes. Results In adolescents who engage in NSSI, negative events on social media were positively associated with perceived stress, negative affect, and NSSI urges to a greater extent than real-life negative events. However, NSSI events during the sampling period were mostly triggered by real-life events. While the frequency of social media use was generally similar between groups, those with NSSI reported experiencing more negative events on social media. Conclusions Our findings highlight the significant impact of social media on the mental health of adolescents who engage in NSSI, possibly exacerbating stress and negative affect more than real-life events. These results underscore the need for targeted interventions addressing online interactions to mitigate NSSI behaviors and improve adolescent mental health. Trial registration This study has been registered at the German Clinical Trials Register (ID: DRKS00025905, https://drks.de/search/en/trial/DRKS00025905 ).